Metacognitive skills in low self-efficacy students: A case study of junior high school students in the using of the Pythagorean theorem - Pathuddin; Azizah, Nurul; Lefrida, Rita; Alfisyahra (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2025)
Metacognitive skills are increasingly acknowledged as a decisive determinant of mathematical proficiency, as they enable students to plan, monitor, and evaluate their cognitive strategies in problem-solving. However, empirical studies rarely focus on how these skills are exhibited by students with low self-efficacy, a population particularly vulnerable to persistent underachievement in mathematics. Addressing this gap, the present study provides novel insights into the metacognitive functioning of low self-efficacy students when engaging with problem-solving tasks, specifically in the context of the Pythagorean Theorem. The study aimed to describe the manifestation of metacognitive skills among junior high school students with low self-efficacy and analyze their problem-solving strategies and underlying thought processes. Employing a descriptive qualitative design, participants were identified as low self-efficacy students using a standardized questionnaire. Data were obtained from self-efficacy questionnaires, problem-solving tasks, and semi-structured interviews, and subsequently analyzed through metacognitive indicators embedded within Polya’s problem-solving framework. Findings indicate that while low self-efficacy students exhibited consistent awareness and evaluative monitoring, their regulatory skills were less developed, particularly in the reviewing stage of problem-solving. Although planning and assessment strategies were evident, frequent errors required iterative adjustments before arriving at correct solutions. These results highlight the intertwined relationship between metacognition and affective-motivational factors, suggesting that mathematics instruction should explicitly integrate self-efficacy enhancement with metacognitive training. The study contributes to advancing the theoretical discourse on mathematics learning and offers practical implications for designing instructional models that accommodate learners with diverse motivational profiles.